Osteoarthritis: What Does Imaging Tell Us about Its Etiology? - Johnson, Victoria L.; Giuffre, Bruno M.; Hunter, David J. (Seminars in Musculoskeletal Radiology, 2012)
Osteoarthritis (OA) is the most common joint disorder and a leading cause of disability. Due to an aging population and increasing obesity, the incidence of OA is rising. The etiology of OA is multifactorial and complex; thus prevention of OA remains challenging. Risk factors can be divided into person-level factors such as age, sex, obesity, genetics, race/ethnicity, and diet, and joint-level factors including injury, malalignment, and abnormal loading of the joints. This review provides a brief overview of the person-level risk factors and a more in-depth analysis of those at the joint level. It is only through an improved understanding of risk factors for the disease that we may be able to intervene meaningfully and prevent its occurrence.
Keywords: osteoarthritis; etiology; radiography